Comparison of Apical and Basolateral Cu Treatment for Iron-Related Gene Regulation During Deferoxamine Induced Iron Deficiency - Güleç, Şükrü; Evcan, Ezgi; Evcan, Ezgi; Güleç, Şükrü (BioMed Central Ltd., 2022)
Background: Intestinal copper transporter (Atp7a) mutant-brindled mice with systemic Cu deficiency had elevated Cu levels in enterocyte cells without any perturbation of iron-regulating genes, suggesting that blood Cu level might be important for intestinal iron homeostasis during iron deficiency (ID). We hypothesized that the blood Cu level and polarization (apical and basolateral) of enterocyte cells might be important regulators for the compensatory response on the regulation of genes in enterocyte cells during iron deficiency. Methods: We grew Caco-2 cells on a bicameral cell culture plate to mimic the human intestine system and on a regular tissue culture plate. Iron deficiency was induced by deferoxamine (DFO). The cells were treated with Cu and Cu with Fe following mRNA expressions of DMT1, FPN, TFR, and ANKRD37 were analyzed. Results: Our main finding was that basolateral treatment of Cu significantly reduced mRNA expressions of iron-regulated genes, including DMT1, FPN, TFR, and ANKRD37, compared to DFO-treated and DFO with apical Cu-treated groups in both bicameral and regular tissue culture plates. Conclusions: Cu level in the basolateral side of Caco-2 cells significantly influenced the intracellular gene regulation in DFO-induced iron-deficient condition, and polarization of the cells might be important factor gene regulation in enterocyte cells.
Keywords: Apical; Anemia; Basolateral; Iron deficiency anemia; Intestine